Discovery of highly excited long-lived isomers in neutron-rich hafnium and tantalum isotopes through direct mass measurements - Reed, Matthew; Cullen, I. J.; Walker, P. M.; Litvinov, Yu. A.; Blaum, K.; Bosch, F.; Brandau, C.; Carroll, J. J.; Cullen, D. M.; Deo, A. Y.; Detwiller, B.; Dimopoulou, C.; et al. (Physical review letters, 2010)
A study of cooled 197Au projectile-fragmentation products has been performed with a storage ring. This has enabled metastable nuclear excitations with energies up to 3 MeV, and half-lives extending to minutes or longer, to be identified in the neutron-rich nuclides 183,184,186Hf and 186,187Ta. The results support the prediction of a strongly favored isomer region near neutron number 116.
Gesehen am 11.05.2023